APPLICATION OF TRADABLE DISCHARGE CREDITS TO WASTEWARTER MANAGEMENT: A FEASIBILITY STUDY - Čekanavičius, Linas (Ekonomika, 2010)
The paper presents results of a field study on the feasibility of applying tradable discharge credits approach to wastewater management. The hypothesis that formed the basis of the present study is that conversion of the existing municipal wastewater discharge management system in Lithuania into the one that uses tradable discharge credits can bring both private and overall (social) economic benefits in the form of increased flexibility of the sewerage subscribers to select the most cost-effective means of compliance with the discharge limits. Research has been conducted in order to determine whether the tradable discharge credits can be employed for municipal wastewater management and, if so, how it can be done. The presented framework of wastewater management, based on tradable discharge credits, can serve as a blueprint for similar applications in other countries or regions, as well as a basis for policy steps.